Talent retention: evidence from a multinational firm in France. Issue 4 (5th June 2017) - Tlaiss, Hayfaa A.; Martin, Pascal; Hofaidhllaoui, Mahrane
Abstract : Purpose: While multinational corporations appear to understand the importance of talent retention (TR) for maintaining their competitive advantage, they continue to struggle to identify and develop strategies to retain talent. Thus, the purpose of this paper is to explore how talent is identified, and more importantly, how it is retained within the context of a multinational firm in France. Design/methodology/approach: This study is exploratory in nature and capitalizes on a case study methodology through which in-depth, open-ended interviews with partners and managers were conducted. Findings: The findings suggest that TR is approached in an arbitrary and ad hoc manner. They also reveal that TR practices are mostly motivated by the direct costs associated with a failure to retain talent, and less with the indirect costs and loss of tacit knowledge. Of considerable interest is the finding that despite the use of utilitarian power via incentives to promote TR, the focus is mostly on normative power via workplace culture and organizational norms. Originality/value: This study is the first to explore TR in the context of one of the Big Four accounting firms in France and among the few to extend the use of Etzioni's (1975) model of compliance to TR research and to a French context. The originality of this study is also derived from its ability to explain the factors impacting TR, how talent is retained in practice, and the gap between the ideals and reality.